Protective effect of acanthospermumhispidumethyl acetate extract on hyperglycemic and glycoprotein components in stz induced diabetic rats - J.VASUNDHARAMMA; J. KAMAKSHAMMA; S.VARALAKSHMI (International Journal of Pharma and Bio Sciences, 2016)
Over the past decade, herbal medicines have been accepted universally, and they have an impact on both world health and international trade. Diabetes mellitus is a metabolic disorder in the endocrine system. This dreadful disease is found in all parts of the world and is becoming a serious threat to mankind health. There are lots of chemical agents available to control and to treat diabetic patients, but total recovery from diabetes has not been reported up to this date. Alternative to these synthetic agents, plants provide a potential source of hypoglycaemic drugs and are widely used in several traditional systems of medicine to prevent diabetes. This study was designed to evaluate the effect of Acanthospermum hispidum ethyl acetate extract on the levels of glycoproteins in STZ -induced diabetic Rats. Albino rats were divided equally into four groups: Group 1: control, Group 2: diabetic control , Group 3: diabetic rats treated with 300 mg/kg body weight of plant extract and group 4 diabetic rats treated with 450 mg/kg body weight of plant extract. All treatments were administered via an intragastric tube. Diabetes was induced in the rats of Group 2 by an intraperitoneal injection with 50 mg/kg body weight of STZ Oral administration of plant extract at a concentration of 300 mg/kg body weight and 450 mg/kg body weight for three weeks (21 days) days significantly reduced the levels of blood glucose, glycosylated hemoglobin, and increased in plasma insulin, body weight, as well as those of hexose, hexosamine, fucose, and sialic acid in the diabetic rats treated with the plant extract as compared to untreated diabetic rats, with no adverse effects in rats treated only with plant extract. In conclusion, Acanthospermum hispidum plant extract proved to have a beneficial effect on the diabetic rats in this study. In light of these advantageous results, it is advisable to broaden the scale of use of Acanthospermum hispidum extract in a trial to alleviate the adverse effects of diabetes.